PDM3, a pentatricopeptide repeat-containing protein, affects chloroplast development. (19th October 2017) - Zhang, Jian; Xiao, Jianwei; Li, Yuqian; Su, Bodan; Xu, Huimin; Shan, Xiaoyi; Song, Chengwei; Xie, Jianbo; Li, Ruili
Abstract : PDM3 is involved in the regulation of the plastid-encoded polymerase-dependent gene expression and RNA splicing that is required for early chloroplast development in Arabidopsis. Abstract: The chloroplast, as the photosynthetic organelle of plants, plays a crucial role in plant development. Extensive studies have been conducted on chloroplast development; however, the related regulatory mechanism still remains elusive. Here, we characterized a mutant with defective chloroplasts in Arabidopsis, termed pigment-defective mutant3 ( pdm3 ), which exhibits a distinct albino phenotype in leaves, eventually leading to pdm3 seedling lethality under autotrophic growth conditions. Electron microscopy demonstrated that the number of thylakoids was reduced and the structure of those thylakoids was disrupted in the pdm3 mutant, which eventually led to the breakdown of chloroplasts. Sequence analysis showed that PDM3 encodes a chloroplast protein consisting of 12 pentratricopeptide repeat domains that belongs to the P subgroup. Both confocal microscopic analysis and immunoblotting in the chloroplast protein fraction showed that PDM3 was located in the stroma. Furthermore, analysis of the transcript profiles of chloroplast genes revealed that plastid-encoded polymerase-dependent transcript levels were markedly reduced, while nuclear-encoded polymerase-dependent transcript levels were increased in pdm3 mutants. In addition, we found that the splicing of introns in trnA, ndhB, and clpP-1 is also affected in pdm3 . Taken together, we propose that PDM3 plays an essential role in chloroplast development in Arabidopsis.